Evaluation of the efficacy of the modified bluegrass appliance in cessation of thumb-sucking habit: an in vivo study with 12 months follow-up - Chhabra, Nidhi; Chhabra, Anuj (Medicine and Pharmacy Reports, 2020)
Background and aims. Blue grass appliance, also known as habit correction roller has gained universal attention and acceptance to correct thumb sucking habit. The present study utilizes the modified bluegrass appliance that was fabricated with an inexpensive acrylic roller to lower the cost of treatment and make it more affordable for the patients in developing countries. The purpose of this study was to evaluate the efficacy of the modified bluegrass appliance in cessation of thumb-sucking habit. Methods. Forty children aged 4-14 years visiting our department for the treatment of thumb sucking habit were selected. A modified bluegrass appliance having an acrylic roller was used along with the positive reinforcement. The patients were followed-up after two weeks of appliance placement and then monthly for twelve months. The various factors like need of reinsertion, discomfort caused due to improper placement or distortion, and/or breakages of the appliance following insertion were evaluated. The cessation of the thumb sucking habit was determined by the patient and/or parental/legal guardian confirmation and disappearance of the callous formation on the thumb. However, the total treatment time was determined when the appliance was removed. Results. Of the total 33 patients included in the final analysis, the treatment was successful in 32 (97%) of the patients. The treatment time for the cessation of habit was ≤ 4 weeks in 13 (40.6 %) patients and 5-20 weeks in 50% of the subjects. Conversely, in 2 (6.3%) of the patients the habit ceased after 21-24 weeks and in 1 (3.1%) patients it took 25-28 weeks for the habit to cease. The appliance had to be reinserted during the treatment in 5 (15.7%) out of the total 32 patients. The total treatment time for the cessation of thumb-sucking habit with modified bluegrass appliance was ≤24 weeks in 17 (53.1%) patients, 25-36 weeks in 34.4% and 37-48 weeks for the 12.5% subjects. Conclusion. The modified bluegrass appliance was found to be highly comfortable and cost saving for the patients and very much successful in eliminating the habit within a short period of time without any complications.